Unplugged Coding Activities for Early Childhood Problem-Solving Skills - Mutoharoh; Hufad, Achmad; Faturrohman, Maman; Rusdiyani, Isti (JPUD - Jurnal Pendidikan Usia Dini, 2021)
Problem solving skills are very important in supporting social development. Children with problem solving skills can build healthy relationships with their friends, understand the emotions of those around them, and see events with other people's perspectives. The purpose of this study was to determine the implementation of playing unplugged coding programs in improving early childhood problem solving skills. This study used a classroom action research design, using the Kemmis and Taggart cycle models. The subjects of this study were children aged 5-6 years in Shafa Marwah Kindergarten. Research can achieve the target results of increasing children's problem-solving abilities after going through two cycles. In the first cycle, the child's initial problem-solving skills was 67.5% and in the second cycle it increased to 80.5%. The initial skills of children's problem-solving increases because children tend to be enthusiastic and excited about the various play activities prepared by the teacher. The stimulation and motivation of the teacher enables children to find solutions to problems faced when carrying out play activities. So, it can be concluded that learning unplugged coding is an activity that can attract children's interest and become a solution to bring up children's initial problem-solving abilities. Keywords: Early Childhood, Unplugged Coding, Problem solving skills References: Akyol-Altun, C. (2018). Algorithm and coding education in pre-school teaching program integration the efectiveness of problem-solving skills in students. Angeli, C., Smith, J., Zagami, J., Cox, M., Webb, M., Fluck, A., & Voogt, J. (2016). A K-6 Computational Thinking Curriculum Framework: Implications for Teacher Knowledge. Educational Technology & Society, 12. Anlıak, Ş., & Dinçer, Ç. (2005). Farklı eğitim yaklaşımları uygulayan okul öncesi eğitim kurumlarına devam eden çocukların kişilerarası problem çözme becerilerinin değerlendirilmesi. Ankara Üniversitesi Eğitim Bilimleri Fakülte Dergis. Aranda, G., & Ferguson, J. P. (2018). Unplugged Programming: The future of teaching computational thinking? Pedagogika, 68(3). https://doi.org/10.14712/23362189.2018.859 Arinchaya Threekunprapa. (2020). Patterns of Computational Thinking Development while Solving Unplugged Coding Activities Coupled with the 3S Approach for Self_Directed Learning. European Journal of Educational Research, 9(3), 1025–1045. Arı, M. (2003). Türkiye’de erken çocukluk eğitimi ve kalitenin önemiNo Title. Erken Çocuklukta Gelişim ve Eğitimde Yeni Yaklaşımlar. Armoni, M. (2012). Teaching CS in kindergarten: How early can the pipeline begin? ACM Inroads, 3(4), 18–19. https://doi.org/10.1145/2381083.2381091 Aydoğan, Y. (2004). İlköğretim ikinci ve dördüncü sınıf öğrencilerine genel problem çözme becerilerinin kazandırılmasında eğitimin etkisinin incelenmesi. Bell, T., Alexander, J., Freeman, I., & Grimley, M. (2009). Computer Science Unplugged: School students doing real computing without computers. 10. Berk, L. E. (2013). Bebekler ve çocuklar: Doğum öncesinden orta çocukluğa. N. Işıkoğlu Erdoğan, Çev. Bers, M. U. (2018). Coding, playgrounds, and literacy in early childhood education: The devel_opment of KIBO robotics and Scratch Jr. IEEE. Brackmann, C. P., Moreno-León, J., Román-González, M., Casali, A., Robles, G., & Barone, D. (2017). Development of computational thinking skills through unplugged activities in primary school. ACM International Conference Proceeding Series, 65–72. https://doi.org/10.1145/3137065.3137069 Brennan, K., & Resnick, M. (2012). New frameworks for studying and assessing the development of computational thinking. 25. Deek, F. P. (1999). The software process: A parallel approach through problem solving and program development. Computer Science Education. Demi̇Rer, V., & Sak, N. (2016). Programming Education and New Approaches Around the World and in Turkey. 26. Dereli-İman. (2014). Değerler eğitimi programının 5-6 yaş çocukların sosyal gelişimine etkisi: Sosyal beceri, psiko-sosyal gelişim ve sosyal problem çözme becerisi. Kuram ve Uygulamada Eğitim Bilimleri. Doğru, M., Arslan, A., & Şeker, F. (2011). Okul öncesinde uygulanan fen etkinliklerinin 5-6 yaş çocukların problem çözme becerilerine etkisi. Uluslararası Türkiye Eğiti Araştırmaları Kongresi. Erickson, A. S. G., Noonan, P., Zheng, C., & Brussow, J. A. (2015). The relationship between self-determination and academic achievement for adolescents with intellectual disabilities. Research in Developmental Disabilities, 36, 45–54. Fee, S. B., & Holland-Minkley, A. M. (2010). Teaching computer science through problems, not solutions. Computer Science Education, 20(2), 129–144. https://doi.org/10.1080/08993408.2010.486271 Futschek, G., & Moschitz, J. (2010). Developing algorithmic thinking by inventing and playing algo_rithms. Gretter, S., & Yadav, A. (2016). Computational Thinking and Media & Information Literacy: An Integrated Approach to Teaching Twenty-First Century Skills. Grover, S., & Pea, R. (2013). Computational thinking in k-12: A review of the state of the field. Educational Researcher. Harrop, W. (2018). Coding for children and young adults in libraries: A practical guide for librarians. 45. Hazzan, O., Lapidot, T., & Ragonis, N. (2011). Guide to Teaching Computer Science. Springer London. https://doi.org/10.1007/978-0-85729-443-2 Horn, M. S., Crouser, R. J., & Bers, M. U. (2012). Tangible interaction and learning: The case for a hybrid approach. Personal and Ubiquitous Computing, 16(4), 379–389. https://doi.org/10.1007/s00779-011-0404-2 Hsu, T.-C., Chang, S.-C., & Hung, Y.-T. (2018). How to learn and how to teach computational thinking: Suggestions based on a review of the literature. Computers & Education, 126, 296–310. https://doi.org/10.1016/j.compedu.2018.07.004 Ismail, M. N., Ngah, N. A., & Umar, I. N. (2010). Instructional strategy in the teaching of computer programming: A need assessment analyses. TOJET: The Turkish Online Journal of Educational Technology. Ismail, M. N., Ngah, N. A., & Umar, I. N. (2010). Instructional Strategy in The Teaching of Computer Programming: A Need Assessment Analyses. The Turkish Online Journal of Educational Technology, 9(2), 7. Jitendra, A. K., Petersen-Brown, S., Lein, A. E., Zaslofsky, A. F., Kunkel, A. K., Jung, P.-G., & Egan, A. M. (2013). Teaching Mathematical Word Problem Solving: The Quality of Evidence for Strategy Instruction Priming the Problem Structure. Journal of Learning Disabilities, 48(1), 51–72. https://doi.org/10.1177/0022219413487408 Joohi Lee. (2019). Coding in early childhood. Contemporary Issues in Early Childhood. Kalyuga, S., Renkl, A., & Paas, F. (2010). Facilitating flexible problem solving: A cognitive load perspective. Educational Psychology Review. Kemmis, S., McTaggart, R., & Nixon, R. (2014). The Action Research Planner. Springer Singapore. https://doi.org/10.1007/978-981-4560-67-2 Kesicioğlu, O. S. (2015). Okul öncesi dönem çocukların kişilerarası problem çözme becerilerinin incelenmesi. Eğitim ve Bilim. Koksal Akyol, A. ve Didin, E. (2016). Ahlak gelisimi [Moral development]. In Cocuk Gelisimi icinde [In Child Development]. Lazakidou, G., & Retalis, S. (2010). Using computer supported collaborative learning strategies for helping students acquire self-regulated problem-solving skills in mathematics. Computers & Education, 54(1), 3–13. https://doi.org/10.1016/j.compedu.2009.02.020 Looi, C.-K., How, M.-L., Longkai, W., Seow, P., & Liu, L. (2018). Analysis of linkages between an unplugged activity and the development of computational thinking. Computer Science Education, 28(3), 255–279. https://doi.org/10.1080/08993408.2018.1533297 McClure, E. R., Guernsey, L., Clements, D. H., Bales, S. N., Nichols, J., Kendall-Taylor, N., & Levine, M. H. (2017). Grounding science, technology, engineering, and math education in early childhood. 68. McLennan, D. P. (2017). Creating coding stories and games. Teaching Young Children. McNerney, TimothyS. (2004). From turtles to Tangible Programming Bricks: Explorations in physical language design. Personal and Ubiquitous Computing, 8(5). https://doi.org/10.1007/s00779-004-0295-6 Mittermeir, R. T. (2013). Algorithmics for preschoolers—A contradiction? Montemayor, J., Druin, A., Chipman, G., Farber, A., & Guha, M. L. (2004). Tools for children to create physical interactive storyrooms. Computers in Entertainment, 2(1), 12–12. https://doi.org/10.1145/973801.973821 Pane, J. F. (2002). A Programming System for Children that is Designed for Usability. 204. Papanastasiou, G., Drigas, A., Skianis, C., Lytras, M., & Papanastasiou, E. (2018). Virtual and augmented reality effects on K-12, higher and tertiary education students’ twenty-29 first century skills. Pellegrino, J. W., & Hilton, M. L. (2012). Education for Life and Work: Developing Transferable Knowledge and Skills in the 21st Century. Pila, S., Aladé, F., Sheehan, K. J., Lauricella, A. R., & Wartella, E. A. (2019). Learning to code via tablet applications: An evaluation of Daisy the Dinosaur and Kodable as learning tools for young children. Computers & Education, 128, 52–62. https://doi.org/10.1016/j.compedu.2018.09.006 Root, J., Saunders, A., Spooner, F., & Brosh, C. (2017). Teaching Personal Finance Mathematical Problem Solving to Individuals with Moderate Intellectual Disability. Career Development and Transition for Exceptional Individuals, 40(1), 5–14. https://doi.org/10.1177/2165143416681288 Scanlan, D. A. (1989). Structured flowcharts outperform pseudocode: An experimental comparison. IEEE Software, 6(5), 28–36. https://doi.org/10.1109/52.35587 Sheehan, K. J., Pila, S., Lauricella, A. R., & Wartella, E. A. (2019). Parent-child interaction and children’s learning from a coding application. Computers & Education, 140, 103601. https://doi.org/10.1016/j.compedu.2019.103601 Shute, V. J., Sun, C., & Asbell-clarke, J. (2017). Demystifying computational thinking. Educational Research Review. Sigelman, C. K., & Rider, E. A. (2012). Life-span Human Development (7th ed.). Cengage Learning. Sullivan, A., & Bers, M. U. (2016). Robotics in the early childhood classroom: Learning outcomes from an 8-week robotics curriculum in pre-kindergarten through second grade. International Journal of Tech_nology and Design Education, 26, 3–20. Sullivan, A. A., Bers, M. U., & Mihm, C. (2017). International conference on com_putational thinking education. Imagining, Playing, and Coding with KIBO: Using Robot_ics to Foster Computational Thinking in Young ChildreImagining, Playing, and Coding with KIBO: Using Robot_ics to Foster Computational Thinking in Young Children. Sullivan, A., Elkin, M., & Bers, M. U. (2015). KIBO robot demo: Engaging young children in programming and engineering. Proceedings of the 14th International Conference on Interaction Design and Children, 418–421. https://doi.org/10.1145/2771839.2771868 Threekunprapa, A., & Yasri, P. (n. d.). (2020). The role of augmented reality based unplugged computer programming approach in the effectiveness of computational thinking. Uysal, A. & Kaya-Balkan, İ. (2015). Sosyal beceri eğitimi alan ve almayan okul öncesi çocukların, sosyal beceri ve benlik kavramı düzeyleri açısından karşılaştırılması. Psikoloji Çalışmaları. Vorderman, C. (2017). Computer coding for kids: A unique step-by-step visual guide, from binary code to building games. Voronina, L. V., Sergeeva, N. N., & Utyumova, E. A. (2016). Development of algorithm skills in preschool children. Procedia-Social and Behavioral Sciences, 233, 155-159. Wang, D., Han, H., Zhan, Z., Xu, J., Liu, Q., & Ren, G. (2015). A problem solving oriented intelligent tutoring system to improve students’ acquisition of basic computer skills. Comput. Educ., 81, 102–112. Wang, D., Zhang, C., & Wang, H. (2010). Proceedings of the 10th international conference on interaction design and children. T-Maze: A Tangible Programming Tool for Children. Wang, Danli, Zhang, C., & Wang, H. (2011). T-Maze: A tangible programming tool for children. Proceedings of the 10th International Conference on Interaction Design and Children - IDC ’11, 127–135. https://doi.org/10.1145/1999030.1999045 Woods, D. R., Hrymak, A. N., Marshall, R. R., Wood, P. E., Crowe, C. M., Hoffman, T. W., Wright, J. D., Taylor, P. A., Woodhouse, K. A., & Bouchard, C. G. K. (1997). Developing Problem Solving Skills: The McMaster Problem Solving Program. Journal of Engineering Education, 86(2), 75–91. https://doi.org/10.1002/j.2168-9830.1997.tb00270.x Yıldırım, A. (2014). Okul öncesinde yaratıcı problem çözme etkinliklerinin yaratıcılığa etkisi (5 yaş örneği). Hacettepe University, Ankara, Turkey. Yohanes. (2018). Mengajarkan Computational Thinking dan Coding Pada Anak-Anak. Amazing Grace. https://blog.compactbyte.com/2018/05/26/mengajarkan-computational-thinking-dan-coding-pada-anak-anak/ Yu, K.-C., Fan, S.-C., & Lin, K.-Y. (2015). Enhancing Students’ Problem-Solving Skills Through Context-Based Learning. International Journal of Science and Mathematics Education, 13(6), 1377–1401. https://doi.org/10.1007/s10763-014-9567-4 Yuksel, H. S. (2019). Experiences of Prospective Physical Education Teachers on Active Gaming within the Context of School-Based Physical Activity. European Journal of Educational Research, 8(1). https://doi.org/10.12973/eu-jer.8.1.199 Zvarych, I., Kalaur, S. M., Prymachenko, N. M., Romashchenko, I. V., & Romanyshyna, O. Ia. (2019). Gamification as a Tool for Stimulating the Educational Activity of Students of Higher Educational Institutions of Ukraine and the United States. European Journal of Educational Research, 8(3). https://doi.org/10.12973/eu-jer.8.3.875